Semi-online scheduling with GoS eligibility constraints - Lee, Kangbok; Hwang, Hark-Chin; Lim, Kyungkuk (International journal of production economics, 2014)
We consider semi-online scheduling problems on parallel machines to minimize the makespan subject to Grade of Service (GoS) eligibility constraints with different prior information: (1) the known total processing time, (2) the known largest processing time, (3) the known both total and largest processing times and (4) the known optimal makespan. For semi-online problems with different numbers of machines and information, we present a unified algorithm. Then we provide lower bounds of the competitive ratio for any algorithm and prove the competitive ratio of the proposed algorithm.